Rationelle klinische Untersuchung der Bandrupturen am oberen Sprunggelenk - Drasnar, V (Zentralblatt fur Chirurgie, 1994)
To eliminate drawbacks of the standard clinical examination technique of the ligamentous lesions of the ankle the author has developed his own method. The position of the patient is prone with bent knee. In evaluating the drawer sign manoeuvres rendering both, the full anterior shift of the foot and palpation of the talus, are used. During x-ray examination the same principles should be observed.
Keywords: Joint Instability; nestabilita kloubu; poranění kotníku; Ligaments, Articular; Humans; Palpation; rozsah kloubních pohybů; kloubní ligamenta; Ankle Injuries; palpace; Range of Motion, Articular; lidé